IMPACT OF MARINE PROTECTED AREAS ON FISHERS' CATCH PRODUCTIVITY AND INCOME: A PROPENSITY SCORE MATCHING ANALYSIS - Mary Cris F. PLEÑOS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Marine Protected Areas or MPAs have been established to protect coastal and marine habitat. This study aims to examine the efficiency of MPAs in the province of Leyte, Philippines. Mann-Whitney U test, a nonparametric analysis, was used to compare fishers both from MPA and non-MPA sites using selected fishing variables. Multiple regression analysis was applied to identify variable/s that significantly influences fish catch and fishing income. Propensity score matching or PSM quantifies the impact of MPAs. Based on the results, in terms of catch, revenue, costs, and travel time to fishing areas MPA sites are significantly higher than non-MPA sites. By regression analysis, only motorized boats showed to significantly increase the catch as well as the income. By PSM, MPA fishing grounds lead to higher fish catch of small-scale fishers which is considered a positive impact of MPA. MPA increases fish catch by 0.3470 kg and income by MPA sites increases their monthly income by PHP 95.44.